Fc functional antibody responses to adjuvanted versus unadjuvanted seasonal influenza vaccination in community-dwelling older adults. Issue 10 (28th February 2020) - Vanderven, Hillary A.; Barr, Ian; Reynaldi, Arnold; Wheatley, Adam K.; Wines, Bruce D.; Davenport, Miles P.; Hogarth, P. Mark; Kent, Stephen J.
Abstract: Background: Seasonal influenza vaccination with a standard trivalent influenza vaccine (TIV) induces a modest, and cross-reactive, Fc functional antibody response in older adults. Recent improvements to influenza vaccines include a quadrivalent influenza vaccine (QIV) and a TIV adjuvanted with the squalene-based oil-in-water emulsion MF59. Methods: Pre- and post-vaccination serum samples from older adults vaccinated with QIV (n = 27) and adjuvanted TIV (n = 44) were studied using hemagglutination inhibition (HAI) assays and dimeric Fc-gamma receptor IIIa binding ELISAs, as a surrogate of antibody-dependent cellular cytotoxicity (ADCC). Results: We found that the unadjuvanted QIV elicited a stronger HAI response against the H1N1 vaccine virus than the adjuvanted TIV. Post-vaccination levels of HA-specific ADCC antibodies were similar for older adults vaccinated with QIV and adjuvanted TIV. The ADCC response to influenza vaccination was largely determined by pre-vaccination or baseline levels of these antibodies, with older adults with low baseline levels of ADCC activity demonstrating greater post-vaccination rises. Conclusions: In this cohort of community-dwelling older adults, the QIV was at least as good as the adjuvanted TIV in the induction of ADCC and HAI responses. Further studies on how these antibody responses translate to efficacy in preventing influenza infections are warranted.